Lipidomics and biochemical profiling of adult Yili horses in a 26 km endurance race: exploring metabolic adaptations - Chang, Xiaokang; Zhang, Zihan; Yao, Xinkui; Meng, Jun; Ren, Wanlu; Zeng, Yaqi (Frontiers in Veterinary Science, 2025)
The equine lipid metabolism is activated during and after endurance exercise to provide energy in response to the metabolic and physiological changes in the body caused by prolonged exercise; however, the specific regulatory mechanisms remain controversial and identifying differential lipid metabolites associated with equine endurance is essential to elucidate these regulatory mechanisms. In this study, blood samples for lipid metabolomic analysis and biochemical indices were collected before and after a 26 km race from 12 Yili horses with different endurance performance. The biochemical results showed that: the albumin (ALB) level was significantly higher in the general group than in the excellent group before the competition, but significantly lower in the ordinary group after the competition (p < 0.05); the pre-competition alanine aminotransferase (ALT) in the excellent group was significantly higher than that of the general group (p < 0.05); and the urea nitrogen (BUN) in the general group was significantly higher than that of the excellent group after the competition (p < 0.05). The lipid metabolism results showed that a total of 1,537 lipid differential metabolites were obtained, mainly enriched in the pathways of fatty acid biosynthesis, cortisol synthesis and secretion, bile secretion, aldosterone regulation of sodium reabsorption, biotin metabolism, steroid hormone biosynthesis, and neuroactive ligand-receptor interactions. Metabolomics and biochemical correlation analyses screened PC (18:3/18:4) and PI (18:1/18:2) as potential biomarkers to identify endurance performance in Yili horses. The results of this study provide a solid foundation for improving equine racing performance and for the selection and breeding of endurance horses by providing a comprehensive reference on the mechanisms of lipid metabolism in equine endurance.